2021
DOI: 10.3390/cells10051043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypothermic Storage Fluids on Mesenchymal Stem Cell Stability: A Comprehensive Review and Personal Experience

Abstract: Mesenchymal stem cells have generated a great deal of interest due to their potential use in regenerative medicine and tissue engineering. Examples illustrating their therapeutic value across various in vivo models are demonstrated in the literature. However, some clinical trials have not proved their therapeutic efficacy, showing that translation into clinical practice is considerably more difficult and discrepancies in clinical protocols can be a source of failure. Among the critical factors which play an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 84 publications
2
15
1
Order By: Relevance
“…Also, autologous MSC therapies are predominant (62.5%) over allogeneic. Similar trends have been also observed in other studies ( 47 , 48 , 324 ). Interestingly, in renal pathologies, BM-MSCs have been mostly used in allogeneic settings (59.4%), while AT-MSCs have been used mostly in an autologous manner (80%) ( Figures 3E i–iii).…”
Section: Considerations For the Gmp-production Of Human Mscs For Kidney Diseasesupporting
confidence: 92%
See 2 more Smart Citations
“…Also, autologous MSC therapies are predominant (62.5%) over allogeneic. Similar trends have been also observed in other studies ( 47 , 48 , 324 ). Interestingly, in renal pathologies, BM-MSCs have been mostly used in allogeneic settings (59.4%), while AT-MSCs have been used mostly in an autologous manner (80%) ( Figures 3E i–iii).…”
Section: Considerations For the Gmp-production Of Human Mscs For Kidney Diseasesupporting
confidence: 92%
“…Cell expansion requires enzyme dissociation and cell subculture, and while the evaluation of the optimal cell confluence may vary among operators, a 70–80% confluence is recommended to be reached before detachment ( 323 ). In general, passage numbers from 1 to 5 are commonly used in clinical trials ( 48 , 324 ) and we have also found similar trends in our search ( Table 2 ). The use of low passage MSCs for therapy is currently preferred to higher passages due to the impact that extended passaging has in decreasing the cell proliferation rates and increasing senescence times ( 242 , 333 337 ).…”
Section: Considerations For the Gmp-production Of Human Mscs For Kidney Diseasesupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were observed for AT-MSCs resuspended in Ringer lactate or Hypo Thermosol when compared to AT-MSCs resuspended in only 0.9% NaCl. Thus, the type of carrier solution used represents an important factor that influences the maintenance of stability of MSC-based medicinal products [47]. In our approach, AT-MSCs do not undergo a cryopreservation procedure (except for the preparation of reference samples of the final product) in relation to other investigators, who added a cryopreservation step to the manufacturing procedure, as summarized by Mazini et al [48].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cell-based therapies emerge as a fast-growing field, and present great potential in tissue/organ repairing/regeneration and cancer treatment 14 , 15 . However, traditional cell-based therapies are frequently compromised by low cell viability and immune rejection between hosts and the cells 83 , 84 . How to achieve precise and controllable delivery of target cells in a convenient manner remains challenging.…”
Section: Mnas Integrated With Living Organismsmentioning
confidence: 99%